Remote-sensed forest fire activity across Mexico and its sensitivity to drought - Cisneros-González, Darío; Zúñiga-Vásquez, José Manuel; Pompa-García, Marín (Instituto de Ecología, A.C., 2018)
Forest fires in México are natural regulators in the dynamics of forest ecosystems. However, their mismanagement can cause catastrophic consequences, affecting critical elements of the ecosystems where they occur. In recent years, official sources have reported an increase in forest fires and affected area. It is very well known that forest fires are widely linked to climatic phenomena. Therefore, the main objective of this study is to evaluate the relationship between drought and fire occurrence in Mexico during the period 2005-2016. The fire data were obtained from Moderate Resolution Imaging Spectroradiometer (Modis) while the source of drought data is from a Standardized Index of Precipitation and Evapotranspiration (SPEI). Through the G statistic of Getis-Ord it was geospatially determined where the highest incidence of fires occur and where the largest affected area is located. Results indicated that fires are clustered in the center of the country along the Sierra Madre del Sur and the Eje Neovolcánico. It is also concluded that the drought is related to the occurrence of forest fires and their affected surface by 32% and 38% respectively. This study contributes to recent research linking the influence of climate phenomena with fire.